Effects of Motivation on Staff Performance and Job Satisfaction in The University of Ilorin Library - Abdulwahab Olanrewaju Issa (Insaniyat : Journal of Islam and Humanities, 2021)
This study examined the effects of motivation on job satisfaction and performance of librarians in University of Ilorin Library. It was observed that many employers have attempted several programs to motivate their employees, yet they have not worked for every category of staff in the library. Descriptive survey design was adopted for the study. The population of the study was made up of professional and paraprofessional librarians, which totaled 46 librarians. Relevant data for the study was collected using questionnaire and a total of 41 out of 46 copies of the questionnaire distributed were returned and found usable for the analysis, which was done by simple percentages and frequency tables. The finding revealed that librarians in job performance can be judged based on time taken to complete task, as well as the accuracy and quality of the work done. The finding confirmed that motivational factors such as opportunity for promotion, good working condition, involvement at work, promotion and financial reward affects the job performance and satisfaction of library staff. The finding revealed that job satisfaction has great influence on job performance. the findings also revealed that general job satisfaction exist among the librarians studied. The study concluded that staff performance and job satisfaction of library staff is dependent on motivation. The study recommended that, the existing constituents of job performance and satisfaction should be sustained/improved by ensuring well-set library goals, increment in salary, existence of training opportunity, sincere and annual appraisal, concrete job description and opportunity to participate in decision-making.